Classification of CHD7 Rare Variants in Chinese Congenital Hypogonadotropic Hypogonadism Patients and Analysis of Their Clinical Characteristics - Sun, Bang; Wang, Xi; Mao, Jiangfeng; Zhao, Zhiyuan; Zhang, Wei; Nie, Min; Wu, Xueyan (Frontiers in Genetics, 2022)
Purpose:CHD7 rare variants can cause congenital hypogonadotropic hypogonadism (CHH) and CHARGE syndrome. We aimed to summarize the genotype and phenotype characteristics of CHH patients with CHD7 rare variants. Methods: Rare sequencing variants (RSVs) were detected by Sanger sequencing in a series of 327 CHH patients and were interpreted and grouped according to the American College of Medical Genetics and Genomics (ACMG) guideline. Detailed phenotyping and genotype-phenotype correlation were analyzed. Results: The RSV detection rate was 11.01% (36/327) in the CHH patients. We identified 30 RSVs and 19 of them were novel. Following ACMG criteria, three variants were pathogenic (P), 4 were likely pathogenic (LP), 3 were of uncertain significance with paradoxical evidence (US1), and 20 were of uncertain significance without enough evidence (US2). All patients (4/4, 100%) with P or LP variants manifested extragonadal symptoms. Conclusion: Addition of 19 novel CHD7 variants expanded the spectrum of variants, and pathogenic or likely pathogenic RSVs were more likely to cause syndromic CHH. For CHH patients carrying CHD7 RSVs, detailed genotyping and phenotyping can facilitate clinical diagnosis and therapy.